2021
DOI: 10.2147/amep.s316201
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Quality of Undergraduate Pharmacy Students’ Researches in Ambo University, Ethiopia: A Qualitative Study from Advisors’ Perspective

Abstract: Background One of the problems facing higher education institutions in developing countries such as Ethiopia is the poor quality of undergraduate students’ academic work. However, there is a scarcity of empirical data on the specific causes of the poor quality of undergraduate study. Therefore, the aim of this research is to explore factors that influence the quality of undergraduate pharmacy students’ research projects at Ambo University in Ethiopia, from the perspective of research advisors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…A similar finding was reported in a study conducted in the United States where more than 90% of PharmD students believed that publications provided a sense of recognition and excellence, with the authors noting that research participation facilitates career advancement ( 43 ). A study conducted among research advisors at Ambo University, Ethiopia, demonstrated that there is an absence of knowledge transfer through publication and presentation which was a potential outcome of poor undergraduate pharmacy students' research projects ( 44 ). It has also been reported that inadequate research mentoring can hinder student research activity and associated outputs ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…A similar finding was reported in a study conducted in the United States where more than 90% of PharmD students believed that publications provided a sense of recognition and excellence, with the authors noting that research participation facilitates career advancement ( 43 ). A study conducted among research advisors at Ambo University, Ethiopia, demonstrated that there is an absence of knowledge transfer through publication and presentation which was a potential outcome of poor undergraduate pharmacy students' research projects ( 44 ). It has also been reported that inadequate research mentoring can hinder student research activity and associated outputs ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sufficiently equipped laboratory facilities are necessary for pharmacy students to develop their skills and allow them to practice and strengthen their skills (Olson et al, 2022). Similar to other universities and faculties in middle-income countries, Jordanian universities and faculties are challenged by limited financial resources, a lack of funds for research projects, and the absence of research leadership (Anderson et al, 2009;Gebremariam & Gadisa, 2021). This study highlighted the importance of equipping laboratories and facilities with state-of-art equipment and instruments in achieving desired competencies and programme learning outcomes.…”
Section: Alnahar Et Almentioning
confidence: 99%
“…Furthermore, the limited attention given to the wellbeing aspect in the professional dialogue of undergraduate thesis supervision calls for a deeper investigation into the role of supervisors in recognising, addressing and mitigating the challenges faced by students (Agricola et al, 2021;Gebremariam & Gadisa, 2021). Recognising and bridging this research gap is not only essential for enhancing the overall student experience but also for promoting a more holistic and supportive approach to academic mentorship.…”
Section: Introductionmentioning
confidence: 99%